Production Delay Analysis in Glucose Manufacturing Using Integrated Risk Methods: Analisis Penundaan Produksi dalam Industri Manufaktur Glukosa Menggunakan Metode Risiko Terpadu - Mokhammad Anggi Syarafi; Hana Catur Wahyuni (Indonesian Journal of Innovation Studies, 2025)
General Background Industrial manufacturing systems require stable production processes to maintain productivity and product quality. Specific Background PT. XYZ experiences significant production delays in liquid glucose processing due to machine performance degradation, raw material issues, employee factors, and consumer-related constraints, resulting in a production decrease of up to 20% from the daily target. Knowledge Gap Previous studies tend to analyze production delays separately, lacking an integrated approach combining root cause identification, risk prioritization, and decision-making. Aims This study aims to identify the causes of production delays, evaluate failure risks, and determine optimal corrective actions using Fishbone Diagram, Failure Mode and Effects Analysis (FMEA), and Analytical Hierarchy Process (AHP). Results The findings indicate that machine maintenance issues and external factors are dominant causes, with the highest Risk Priority Number (RPN) identified in the filtration and ion exchanger process (192). AHP analysis shows that dismantling and repairing the heating pipeline is the top-priority solution with a weight of 67.4%. Novelty This study integrates Fishbone, FMEA, and AHP methods to provide a structured and multi-criteria decision-making framework in glucose production systems. Implications The results support improved maintenance planning and production management strategies to reduce delays and maintain operational stability in manufacturing environments. Keywords: Production Delay, Glucose Manufacturing, Risk Analysis, FMEA, AHP Key Findings Highlights Critical failures identified in filtration system with highest risk ranking Multi-method integration enables structured decision prioritization Pipeline repair strategy becomes dominant corrective action